Africa's ‘miracle state'? the intersection of political leaders and non-state actors in the greening of Botswana through wildlife - Mogende, Emmanuel (Department of Environmental and Geographical Science, 2021)
The premise of the thesis is that attention to the processes that produce the green state opens up avenues for analysing African states from the perspective of the green state. This study engages the theory of the green state within the African context to understand the complex processes that enabled the greening of the state in Botswana. I draw on the example of wildlife conservation policies and practices in post-independence Botswana to argue that the greening of the state entails processes by which the state interacts with non-state actors to enact environmental reforms over a long period of time. Such interaction maybe initiated by the state or by non-state actors who are determined to pursue an environmental agenda or to implement environmental strategies through organs of the state. To account for the processes that enable the greening of Botswana, the study employed an interpretive approach that is dependent on qualitative data. The study primarily draws from archival research and key informant interviews with academics, environmental consultants, representatives of civil society, relevant government departments and ministries, the private sector in Botswana's tourism, and an interview with former President Ian Khama. To understand the greening processes, the thesis analysed the qualitative data between 1966 and 2018. These historical periods cover the presidency of Seretse Khama (1966 – 1980), Ketumile Masire (1980 – 1998), Festus Mogae (1998 – 2008) and Ian Khama (2008 – 2018). The four key findings of the study are that, first, the collaboration between authorities in Botswana and international agencies and actors enabled the greening of Botswana. These agencies and actors, financed environmental related programmes, facilitated the development of green institutions, and influenced the country's conservation policies. Second, the study demonstrates that political leadership is instrumental in the greening of Botswana. The four presidencies paid attention to environmental protection though there were variations in each presidency. The presidency of Ian Khama stands out as an important period in greening of the state as he strengthened the greening process by realigning the wildlife economy with political power. Third, the study found that the greening process necessitates the internal restructuring of the state through the establishment of green institutions, which serve to realign state activities with the green agenda. Fourth and lastly, the study reveals that the greening of the state in Botswana is accompanied by negative state-citizen relations in the wildlife sector. These relations played out through the marginalization of the local people in the ecotourism enterprise within the context of community-based natural resource management initiative.